Effect of Wii Fit Exercise With Balance and Lower Limb Muscle Strength in Older Adults: A Meta-Analysis - Liu, Haoyan; Xing, Yu; Wu, Ying (Frontiers in Medicine, 2022)
Objective: To evaluate the current literature by using meta-analyses to assess whether Wii Fit exercise is associated with improved balance and lower limb muscle strength in older adults. Methods: We searched PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, and Wanfang Data from inception to February 16, 2022, for relevant studies and conducted a manual search of the literature. Data extraction of the included studies were independently performed by two authors. The methodologic quality of each included study was assessed using the Physical Therapy Evidence Database (PEDro) scale. Meta-analyses were conducted using Review Manager 5.3. Results: Of 991 articles initially identified, 10 articles (379 participants; aged ≥65 years, range 65-92 years; 188 participants in Wii Fit exercise groups, and 191 participants in control groups), including 8 randomized controlled trials, were assessed in this meta-analysis. The methodologic quality of the included studies evaluated with the PEDro average score was 6.4 and ranged from 5 to 8 points, indicating moderate quality. Compared with no exercise, Wii Fit exercise was associated with improved scores on the Berg Balance Scale, which evaluates functional balance (mean difference, 1.38; 95% CI, 0.61 to 2.16; I² = 31%; P = 0.0005) and on the Timed Up and Go test, which evaluates static and dynamic balance (standardized mean difference, −0.51; 95% CI,−0.88 to −0.14; I² = 52%; P = 0.007). However, for the three studies assessed, Wii Fit exercise did not significantly improve scores on the 30-second chair stand test, which evaluates the functional strength and endurance of the lower limb muscles (mean difference, 0.82; 95% CI, −0.14 to 1.77; z = 1.68; P ＝ 0.09). Conclusions: Our findings indicated that Wii Fit exercise is an effective approach to improve functional, static, and dynamic balance among older adults. Additional meta-analyzes with higher numbers of randomized controlled trials are suggested to confirm the benefits of Wii Fit exercise on balance in older adults, to establish whether functional strength and endurance of lower limb muscles are improved, and to explore the relationship between improved balance and fall prevention in this population.